PERTUMBUHAN TUMPANGSARI JAGUNG DAN KEDELAI PADA PERBEDAAN WAKTU TANAM DAN PEMANGKASAN JAGUNG - Indah Permanasari; Dody Kastono (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
The arrangement of planting time and corn defoliation is one of the efforts for increasing growth of corn and soybean in intercropping system. The purpose of this research was to study the effect of planting time and corn defoliation and their interaction to growth on corn and soybean and comparise the intercropping and monoculturer system. The experimental design used was factorial with two factors (2 x 3) + 2 monoculture treatments under randomize completed block design with tree replications. The first factor was planting time with two levels i.e. planting corn and soybean in the same time and planting corn 10 days after the soybean. The second was corn defoliation with three levels i.e. no defoliation, defoliation with four leaves left above the cob and defoliation of the adjacent and above corn cob. The results showed that growth of corn and soybean did not affected by planting time but the growth of corn was affected by corn defoliation. Plant height of corn on 6 and 9 weeks after planting was significantly increased when the corn planted 10 days after soybean and corn defoliation with four leaves left above the cob but this treatment was decreased dry weight plant. Intercropping system was not decreased leaf area and dry weight plant of corn and soybean.